Intelligent mobile augmented reality application - Song, Chenxing (2017)
Augmented Reality (AR) is a technology that superimposes computer-generated images on top of real world objects. AR extends a variety of experiences and provides useful information to users. Nowadays, AR and VR has become one of the most important research fields in computer science and having an extremely extensive application in the industrial production. For example, with the help of augmented reality technology, online shopping could be much more user-friendly and convenience to customers. Commodities will be visually shown on the mobile phones or computers to customers. All the details of the goods will be shown together with the environment around users. Customers will find it is easy to make a wise choice. Inspired by this, the project aims to build a well-developed mobile application on both IOS and Android system. The application is focused on furniture industry and is supposed to solve real world problems. In this formal report, firstly, the project’s motivation and scope will be discussed. Secondly, how the project is being set up and design, SDK and IDE used, and developing processes will be covered. At last, the report will make a conclusion of the whole project and discuss the future work.